The Effect Of Liquidity, Profitability, And Solvency On Company Value - Meilany Angreni; Gracia Lavenia Tampubolon; Tarves Tanjugo malau; Rizka Handayani; Fitri Yani Panggabean (INFOKUM, 2025)
This study examines the effect of liquidity, profitability, and solvency on company value in publicly listed firms. Financial performance is a crucial factor influencing investor perceptions and corporate valuation, making it essential to analyze how these three financial indicators impact firm value. The research employs quantitative methods, utilizing financial ratio analysis, including Current Ratio (CR) for liquidity, Return on Assets (ROA) and Return on Equity (ROE) for profitability, and Debt to Equity Ratio (DER) for solvency. Secondary data from financial statements of selected companies is analyzed using multiple regression analysis to determine the significance and strength of the relationships between these variables. The findings indicate that liquidity, profitability, and solvency significantly influence company value, though their effects vary. Profitability (ROA & ROE) has the strongest positive impact, suggesting that firms with higher profitability are more attractive to investors. Solvency (DER) shows a negative relationship, indicating that excessive debt may reduce firm value due to higher financial risk. Meanwhile, liquidity (CR) has a mixed effect, depending on the firm's ability to balance short-term obligations with long-term growth. This study provides valuable insights for investors, financial managers, and policymakers in understanding the key financial factors that drive company value. Enhancing profitability while maintaining optimal liquidity and solvency levels is essential for sustainable business growth and increased market valuation.